Improvement in Quality of Service Against Doppelganger Attacks for Connected Network. - Choudhary, Deepak; Pahuja, Roop (International Journal of Interactive Multimedia and Artificial Intelligence, 2022)
Because they are in a high-risk location, remote sensors are vulnerable to malicious ambushes. A doppelganger attack, in which a malicious hub impersonates a legitimate network junction and then attempts to take control of the entire network, is one of the deadliest types of ambushes. Because remote sensor networks are portable, hub doppelganger ambushes are particularly ineffective in astute wellness contexts. Keeping the framework safe from hostile hubs is critical because the information in intelligent health frameworks is so sensitive. This paper developed a new Steering Convention for Vitality Effective Systems (SC-VFS) technique for detecting doppelganger attacks in IoT-based intelligent health applications such as a green corridor for transplant pushback. This method’s main advantage is that it improves vitality proficiency, a critical constraint in WSN frameworks. To emphasize the suggested scheme’s execution, latency, remaining vitality, throughput, vitality effectiveness, and blunder rate are all used. To see how proper the underutilized technique is compared to the existing Half Breed Multi-Level Clustering (HMLC) computation. The suggested approach yields latency of 0.63ms and 0.6ms, respectively, when using dead hubs and keeping a strategic distance from doppelganger assault. Furthermore, during the 2500 cycles, the suggested system achieves the highest remaining vitality of 49.5J.